International Community Service Activities (PkM) in Sekolah Indonesia Kuala Lumpur (SIKL) - Sri Yuliani; Yulianto (Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
The purpose of this International Community services in SIKL was to give a service in socialization of international engagement in International education MoU. Education is a process of socialization, namely socializing values, knowledge, and skills in life. Learning is a product of the citizens themselves, that is, they can live without changing address future threats and challenges (Mufida, 2018). As for SIKL itself, they have the view that the progress of a country depends on the education of its young generation and they also have the paradigm that the success of a student is influenced by educators who teach in schools. Socialization and introduction of the program was delivered during the activities of PkM. The result of this PkM activity was motivating the students and also staffs in SIKL managements in executing the implementation of international collaboration